2018
DOI: 10.2147/idr.s184877
|View full text |Cite
|
Sign up to set email alerts
|

The association between platelet indices and deep surgical site infection after open induction internal fixation for traumatic limb fractures

Abstract: ObjectivesDeep surgical site infection (DSSI) is one of the most serious complications after open induction internal fixation (ORIF) for traumatic limb fractures. In this study, we aimed to investigate the diagnostic role of platelet indices (platelet count [PLT], mean platelet volume [MPV], and platelet distribution width [PDW]) in DSSI.Patients and methodsData obtained between January 2011 and December 2017 in The Affiliated Drum Tower Hospital of Nanjing University Medical School from cases (n=29) with DSSI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Increased PDW was seen in ascitic fluid infection, vivax malaria, dengue, and septic shock [5,9,13,14]. PDW was reduced in deep-seated surgical site infection in orthopaedic patients and children with Gram-positive organism-related urinary tract infection [6,10]. In our study, there was no difference in PDW among patients with MODS and those without.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…Increased PDW was seen in ascitic fluid infection, vivax malaria, dengue, and septic shock [5,9,13,14]. PDW was reduced in deep-seated surgical site infection in orthopaedic patients and children with Gram-positive organism-related urinary tract infection [6,10]. In our study, there was no difference in PDW among patients with MODS and those without.…”
Section: Discussionsupporting
confidence: 41%
“…Platelet indices have been used in the diagnosis and prognosis of various inflammatory, infective, and malignant disorders [ 1 ]. Infections that have been studied include septic shock [ 5 ], urinary tract infection [ 6 ], tuberculosis [ 7 ], H. pylori [ 8 ], spontaneous bacterial peritonitis [ 9 ], surgical site infections [ 10 ], hepatitis [ 11 ], pneumonia [ 12 ], malaria [ 13 ], and dengue [ 14 ]. Platelet indices have not been previously studied in patients with scrub typhus, and hence we hypothesized whether these indices could predict multiorgan dysfunction syndrome in scrub typhus.…”
Section: Introductionmentioning
confidence: 99%
“…If not promptly diagnosed and managed, permanent loss of function, amputation, and even death may result 1. However, in the absence of any reliable method for diagnosing infection prior to nonunion surgery, surgeons cannot accurately discriminate between infected nonunion and aseptic nonunion 8,9. The Association for Osteosynthesis/Association for the Study of Internal Fixation (AO/ASIF) consensus definition of fracture-related infection includes four confirmatory criteria and six suggestive criteria 2.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies have highlighted that PLTs are associated with certain infectious and inflammatory diseases. 20,21 Zhang et al 22 proposed that the PLT distribution width combined with the PLT count can be used as an important additional detection method for the diagnosis of deep SSI after traumatic limb fracture surgery, thereby reducing the cost and time loss. The present study showed a strong correlation between the PLT count and changes in the femoral neck fracture time in immunocompromised patients (R ¼ 0.99, P < 0.05).…”
Section: Discussionmentioning
confidence: 99%